Sponges from a section of the Upper Triassic Nayband Formation, northeast of Esfahan - Rashidi, Koorosh; Senowbari-Daryan, Baba (Annalen des Naturhistorischen Museums in Wien : A, Mineralogie, Petrologie, Geologie, Paläontologie, Archäozoologie, Anthropologie, Prähistorie, 2011)
Hypercalcified sponges, including "Sphinctozoans" and "Inozoans" are described in details from the biocostructions in an Upper Triassic (most probably Rhaetian in age) section of the Nayband Formation, exposed in the northeast area of Esfahan, central Iran. Some chaetetid and spongiomorphid sponges are indentified and described informally. Hexactinellid sponges are extremely rare and are represented by only two connected lattices and in some thin sections by isolated loose spicules. The reefs and reefal limestones in the lower part of the section are dominated by hypercalcified sponges; the upper part of the section is characterized by the dominance of the red algae (Solenoporaceans). Horizontally growing sheets of spongiomorphids are very abundant in some carbonate beds. Hypercalcified sponges occur with at least 25 genera and almost 38 species including 14 sphinctozoan genera and 23 species (three of them as new and two of them as gen. et sp. indet), six inozoan genera with 8 species (one as uncertain genus and species), five chaetetid species and at least two species of spongiomorphids. Two representatives of hexactinellids occur in the investigated section of the Nayband Formation. The following species are described as new: "Sphinctozoa": Amblysiphonella bisiphonata, A. torabii, and Parauvanella spinosa. Inozoa: Peronidella pilleri. Coralline Schwämme, einschließlich die "Sphinctozoen" und "Inozoen", der obertriassischen (höchstwahrscheinlich rhätischen Alter) Biokonstruktionen der Nayband-Formation nordöstlich der Stadt Esfahan (Zentraliran) werden systematisch beschrieben. Einige Chaetetiden und Spongiomorphiden können nur als gen. et sp. indet bestimmt werden. Hexactinelliden Schwämme sind extrem selten und nur durch zwei zusammenhängende Skelettgitter und einige lose Skleren vertreten. Die Riffe und riffoide Karbonate im Liegenden des untersuchten Profils werden durch die Dominanz der corallinen Schwämme, die hangenden Teile des Profils jedoch durch das Vorherrschen der Rotalgen (Solenoporaceen) charakterisiert. Horizontal wachsende, plattige Spongiomorphiden sind in einigen Karbonatbänken des Profils gesteinsbildend. Coralline Schwämme treten im untersuchten Material mit mindestens 25 Gattungen und etwa 38 Arten auf. Es sind 14 Gattungen und 23 Arten den Sphinctozoen (drei von ihnen als neue Arten und zwei als Gen. et sp. indet), sechs Gattungen und acht Arten den Inozoen (eine als unsichere Gattung und Art), fünf Arten den Chaetetiden und schließlich zwei Arten den Spongiomorphiden zuzuordnen. Hexactinelliden Schwämme sind mit zwei Arten vertreten. Folgende Arten werden neu beschrieben: „Sphinctozoa”: Amblysiphonella bisiphonata, A. torabii und Parauvanella spinosa; „Inozoa”: Peronidella pilleriv
UnivIS-Import:2017-11-07:Pub.2011.nat.dgeo.IGM.LP.sponge
Keywords: Sponges; Skeleton; Geology; Canals; Inhalants; Genera; Holotypes; Fauna; Paleontology; Mathematical minima